Leakage Impact On Non Revenue Water (Nrw) In Sungai Petani (Kedah Tengah District), Kedah Darul Aman - Mohamad Saad, Mohd Zaidi (2014)
Leakage is well known as the main reason of high physical loss in non-revenue water (NRW) and is divided into major and minor leakages. A leakage study was done in 10 District Meter Zones (DMZs) in Sungai Petani, Kedah. NRW data had been collected in cooperation with Syarikat Air Darul Aman (SADA). Data taken from year 2008 until2012 were used to investigate the major and minor leakages by doing visual inspection at site and analysis of the results were done. The baseline inflow and baseline average water consumption in cubic meter per day were collected from the Primayer 'data logger' and SADA billing systems to determine the real water losses. Statistical analysis were used to study the relationship between number of leakage with NRW cost saving, number of connection and length of pipe by using the Statistical Product and Service Solution (SPSS).